Use of Autologous Stem Cells in Lumbar Spinal Fusion: A Systematic Review of Current Clinical Evidence. Issue 8 (October 2021) - Buser, Zorica; Hsieh, Patrick; Meisel, Hans-Joerg; Skelly, Andrea C.; Brodt, Erika D.; Brodke, Darrel S.; Park, Jong-Beom; Yoon, S. Tim; Wang, Jeffrey; ,
Study design: Systematic review. Objectives: To systematically review, critically appraise and synthesize evidence on use of autologous stem cells sources for fusion in the lumbar spine. Methods: A systematic search of PubMed/MEDLINE, EMBASE andClinicalTrials.gov through February 20, 2020 was conducted comparing autologous cell grafts to other biologics for lumbar spine fusion. The focus was on studies comparing distinct patient groups. Results: From 343 potentially relevant citations, 15 studies met the inclusion criteria set a priori. Seven studies compared distinct patient groups, with BMA being used in combination with allograft or autograft not as a standalone material. No economic evaluations were identified. Most observational studies were at moderately high risk of bias. When used for primary lumbar fusion, no statistical differences in outcomes or complications were seen between BMA+autograft/or +allograft compared to autograft/allograft alone. Compared with allograft, data from a RCT suggested statistically better fusion and lower complication rates with concentrated BMA+allograft. When used in revisions, no differences in outcomes were seen between BMA+allograft and either autograft or rh-BMP-2 but fusion rates were lower with BMA+allograft, leading to additional revision surgery. Conclusions: There was substantial heterogeneity across studies in patient populations, sample size, biologic combinations, and surgical characteristics making direct comparisons difficult. The overall quality of evidence for fusion rates and the safety of BMA in lumbar fusion procedures was considered very low, with studies being at moderately high or high risk of bias.